Visit-to-Visit Blood Pressure Variability Is Associated With Cognitive Decline and Incident Dementia: The S.AGES Cohort. Issue 4 (October 2020) - Rouch, Laure; Cestac, Philippe; Sallerin, Brigitte; Piccoli, Matthieu; Benattar-Zibi, Linda; Bertin, Philippe; Berrut, Gilles; Corruble, Emmanuelle; Derumeaux, Geneviève; Falissard, Bruno; Forette, Françoise; Pasquier, Florence; et al.
Abstract : To investigate the impact of visit-to-visit systolic blood pressure variability (BPV), diastolic BPV, mean arterial pressure variability, and pulse pressure variability on cognitive decline and incident dementia in noninstitutionalized patients aged ≥65 years. A total of 3319 subjects from the S.AGES (Sujets AGÉS—Aged Subjects) cohort underwent clinical examinations every 6 months during 3 years. Variability was evaluated using standard deviation (SD), coefficient of variation, average real variability, successive variation, variation independent of mean, and residual SD. Cognition was assessed using the Mini-Mental State Examination and dementia with the Diagnostic Statistical Manual of Mental Disorders. Linear mixed models and Cox proportional hazards models were used. Higher systolic BPV was associated with poorer cognition independently of baseline SBP: adjusted 1-SD increase of coefficient of variation: β (SE)=−0.12 (0.06), P =0.04. Similar results were observed for diastolic BPV and mean arterial pressure variability: β (SE)=−0.20 (0.06), P <0.001 for both. Higher pulse pressure variability was no longer associated with cognitive function after adjustment for age, except with residual SD ( P =0.02). Among the 3319 subjects, 93 (2.8%) developed dementia. Higher systolic BPV was associated with greater dementia risk (adjusted 1-SD increase of coefficient of variation: hazard ratios=1.23 [95% CI, 1.01–1.50], P =0.04). Similar results were found for diastolic BPV and mean arterial pressure variability ( P <0.01). Pulse pressure variability was not associated with dementia risk. Beyond hypertension, higher BPV is a major clinical predictor of cognitive impairment and dementia. Further studies are needed to assess whether controlling BP instability could be a promising interventional target in preserving cognition among older adults. Abstract : Supplemental Digital Content is available in the text.